Answer:
im on the same one if i get it right i will comment and tell u k?
Step-by-step explanation:
kk
Answer:
4.8278117e+22
Step-by-step explanation:
![xe^y+4\ln y=x^2](https://tex.z-dn.net/?f=xe%5Ey%2B4%5Cln%20y%3Dx%5E2)
Differentiate both sides with respect to <em>x</em>, assuming <em>y</em> = <em>y</em>(<em>x</em>).
![\dfrac{\mathrm d(xe^y+4\ln y)}{\mathrm dx}=\dfrac{\mathrm d(x^2)}{\mathrm dx}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28xe%5Ey%2B4%5Cln%20y%29%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B%5Cmathrm%20d%28x%5E2%29%7D%7B%5Cmathrm%20dx%7D)
![\dfrac{\mathrm d(xe^y)}{\mathrm dx}+\dfrac{\mathrm d(4\ln y)}{\mathrm dx}=2x](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28xe%5Ey%29%7D%7B%5Cmathrm%20dx%7D%2B%5Cdfrac%7B%5Cmathrm%20d%284%5Cln%20y%29%7D%7B%5Cmathrm%20dx%7D%3D2x)
![\dfrac{\mathrm d(x)}{\mathrm dx}e^y+x\dfrac{\mathrm d(e^y)}{\mathrm dx}+\dfrac4y\dfrac{\mathrm dy}{\mathrm dx}=2x](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28x%29%7D%7B%5Cmathrm%20dx%7De%5Ey%2Bx%5Cdfrac%7B%5Cmathrm%20d%28e%5Ey%29%7D%7B%5Cmathrm%20dx%7D%2B%5Cdfrac4y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D2x)
![e^y+xe^y\dfrac{\mathrm dy}{\mathrm dx}+\dfrac4y\dfrac{\mathrm dy}{\mathrm dx}=2x](https://tex.z-dn.net/?f=e%5Ey%2Bxe%5Ey%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%2B%5Cdfrac4y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D2x)
Solve for d<em>y</em>/d<em>x</em> :
![e^y+\left(xe^y+\dfrac4y\right)\dfrac{\mathrm dy}{\mathrm dx}=2x](https://tex.z-dn.net/?f=e%5Ey%2B%5Cleft%28xe%5Ey%2B%5Cdfrac4y%5Cright%29%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D2x)
![\left(xe^y+\dfrac4y\right)\dfrac{\mathrm dy}{\mathrm dx}=2x-e^y](https://tex.z-dn.net/?f=%5Cleft%28xe%5Ey%2B%5Cdfrac4y%5Cright%29%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D2x-e%5Ey)
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{2x-e^y}{xe^y+\frac4y}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B2x-e%5Ey%7D%7Bxe%5Ey%2B%5Cfrac4y%7D)
If <em>y</em> ≠ 0, we can write
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{2xy-ye^y}{xye^y+4}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B2xy-ye%5Ey%7D%7Bxye%5Ey%2B4%7D)
At the point (1, 1), the derivative is
![\dfrac{\mathrm dy}{\mathrm dx}\bigg|_{x=1,y=1}=\boxed{\dfrac{2-e}{e+4}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%5Cbigg%7C_%7Bx%3D1%2Cy%3D1%7D%3D%5Cboxed%7B%5Cdfrac%7B2-e%7D%7Be%2B4%7D%7D)
Answer: left 9 and up 6
Step-by-step explanation:
just if it’s in the bars it’s left if + and on the outside its up if +
After running for 18 minutes, Julissa completes 2 kilometers. If she is running a 10-kilometer race at a constant pace, then she comletes 1 kilometer after running 9 minutes. Now you can find the distance she run after 1 minute. This is
km.
Let t be the time in minutes. Then k, the number of kilometers, can be found from proportion:
- 1 minute
k km - t minutes.
Thus,
Answer: